(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Objective: Cross-sectional descriptive study. Analysis of some factors affecting full and scheduled vaccination of children under 1 year old in 4 communes in extremely difficult areas of Yen Chau district, Son La province in 2023.Method: Combining quantitative and qualitative research: direct interviews with 252 mothers with children aged 12-24 months; 10 targeted in-depth interviews with mothers, health workers and leaders of district health centers to understand the factors affecting the rate of full and on-schedule vaccination of children.Results: Factors that help children be vaccinated fully and on schedule: living in lowland areas is 2.15 times higher than in highland areas; the Thai ethnic group is 9.4 times higher than the Xinh Mun ethnic group; mothers who are farmers are 2.1 times more likely than mothers who work in other occupations; families located 1-5 km from a vaccination station/point are 2.3 times more likely to be less than 1 km away; mothers with correct knowledge about vaccination schedules are 1.95 times more likely than mothers with incorrect knowledge; children who do not get sick are 2.1 times and 5.6 times higher than children who get sick 1-2 times and children who get sick 3 or more times a year; source of information about vaccination from health workers (97.2%); vaccination outside the clinic is 2.1 times higher than vaccination at the health station; rating easy access to vaccination services is 2.56 times higher than rating difficult to access; the psychology of mothers who are not worried about reactions after vaccination and are not afraid of COVID-19 infection is 5 times higher than mothers who are worried and afraid.Conclusions: Factors that help children in the 4 study communes to be vaccinated fully and on schedule: living in a lowland area, Thai ethnicity, mother being a farmer, house 1-5 km from vaccination station/point, mother have correct knowledge and care about vaccination for children, children do not get sick during the year, health workers provide information about vaccination, off-site vaccination, easy access to vaccination services, no worries post-injection reactions and no fear of COVID-19 infection.